Performance-Based Concept for Design of Structural Silicone Joints in Façades Exposed to Earthquake - V. Nardini (Challenging Glass Conference, 2016)
Façade failure due to seismic event represents a potential hazard to people and can cause serious damages to buildings with consequent high-cost remedial works. As a result, interest in the design of buildings and façades to resist seismic loads and displacements has increased. Current standards and literature recognize the benefits offered by Structural Sealant Glazing (SSG) systems to enhance the performance of unitized curtain walls exposed to earthquake but no precise criteria are available for the seismic design of the structural silicone joints. This paper proposes a design concept to evaluate the effect of forces and displacements imposed to the structural joints due to panel seismic racking; referring to the design philosophy developed by Japanese Standard, the concept is engineered based on three performance levels associated to different design requirements which aim at balancing costs and risks with no compromise on safety. Tensile and shear tests performed on sealant H-specimens and Hockman cycle tests simulating accelerated life cycles at different deformation rates are used to exploit the deformation capability of the joints correlated to residual strengths. Results from static racking tests on full-scale façade panels are used to validate the proposed design concept.